«To the vassals of this yndic continent»: General visit, population and Bourbon reformism in the District of Arica, 1793-1796 - Choque Mariño, Carlos (2024)
The implementation of the Bourbon reforms in the viceroyalty of Peru sought to limit the power of the viceroys and the influence of the Peruvian elite on the government, installing for this purpose greater control over the territory from the perspective of the ministers of the Council of the Indies. In this context, the general visit of the mayor Antonio Álvarez y Ximénez to the district of Arica, made between 1793 and 1796, aimed at understanding the state of the province and solving problems linked to the economy, population, justice, security and colonial bureaucracy. The purpose of this article is to describe and analyze part of the implementation of the Bourbon reforms in the Arica district, and its political, economic and social consequences.